Concussion knowledge, attitudes, and self-reporting intentions in youth athletes - Chandran, A.; Nedimyer, A. K.; Kerr, Z. Y.; O'Neal, C.; Mensch, J.; Yeargin, S. W. (Journal of Athletic Training, 2020)
Context: Although it has been suggested that developmental and sociological factors play a role in concussion reporting, the empirical evidence related to this is limited. Objective: To examine the influences of sex, school level, school location, concussion-reporting history, and socioeconomic status on concussion-related knowledge, attitudes, and reporting intentions among middle school and high school athletes. Design: Cross-sectional study. Setting: Master students and High School athletes attending pre-participation examinations (PPEs) were asked to complete paper-based surveys. Patients or Other Participants: Overall, 541 athletes representing 18 sports returned fully completed surveys. Main Outcome Measure(s): Outcomes were concussion-related knowledge, perceived seriousness, positive feelings about reporting, and self-reporting intentions. We examined group differences in these outcomes across levels of the explanatory variables of sex, school level (middle school versus high school), school location (urban versus rural), concussion self-reporting history (yes or no), and socioeconomic status (free or reduced-price lunch versus no free or reduced-price lunch) using Wilcoxon rank sum tests. Then we used multivariable ordinal logistic regression models to identify predictors of higher score levels for each outcome. Odds ratio (OR) estimates with 95% confidence intervals (CIs) excluding 1.00 were deemed significant. Results: Odds of higher levels of knowledge were higher in urban versus rural school student-athletes (ORAdjusted = 1.81; 95% CI = 1.03, 3.17), and lower in student-athletes on free or reduced-price lunch versus those not on free or reduced-price lunch (ORAdjusted = 0.52; 95% CI = 0.36, 0.77). Similarly, odds of higher levels of seriousness were lower in male versus female student-athletes (ORAdjusted = 0.48; 95% CI = 0.32, 0.72). Further, odds of higher levels of self-reporting intentions were lower among male versus female student-athletes (ORAdjusted = 0.53; 95% CI = 0.37, 0.75). Conclusions: Developmental and sociological factors were differentially associated with concussion-related knowledge, attitudes, and self-reporting intentions. These results can inform medical providers, parents, and coaches with regard to context-specific clinical assessments of concussion symptoms.